The way things work now : from levers to lasers, windmills to Wi-Fi, a visual guide to the world of machines - Macaulay, David; Ardley, Neil (Boston : Houghton Mifflin Harcourt, 2016)
Text and numerous detailed illustrations introduce and explain the scientific principles and workings of hundreds of machines. Includes new material about digital technology.
The mechanics of movement -- Harnessing the elements -- Working with waves -- Electricity & automation -- The digital domain -- Eureka! The invention of machines -- Technical terms.
Originally published as The new way things work.
Kirkus Starred, August 2016
Includes index.
7.0
5-8
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Technology; Technology; Inventions